Detection and separation methods for resolution of products of enzymatic reactions - Meyer, Elazar (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
Special analytical methods have been developed for the detection and separation of the resolved products of several kinetic enzymatic resolutions employing enzymes such as lipases and transglutaminase, which are useful as catalysts in nearly anhydrous organic solvents to carry out stereospecific and selective enzymatic resolutions of compounds such as (+/-)-2-bromohexadecanoic acid (2-Br-HDA), (R,S)-mandelic acid, DL-β-phenyllactic acid and (R,S)-2-phenylpropionic acid.